PENGARUH PEMBERIAN CERAMAH DENGAN MEDIA LEAFLET DALAM MENINGKATKAN PENGETAHUAN TENTANG KAKI BENGKAK - Handayani, Afriagus; Margono, Margono; Hernayanti, Munica Rita (Poltekkes Kemenkes Yogyakarta, 2015)
The causes of maternal deaths are largely due to bleeding during childbirth. Bleeding during labor may be caused, among others, due to anemia pregnant women, in addition to other diseases such as hypertension resulting in eclampsia. Eclampsia is the result that would occur during labor in patients with preeclampsia, which is accompanied by thorough seizures and coma. Similarly, pre-eclampsia, eclampsia can occur in ante, intra, and postpartum. Postpartum eclampsia generally only occurs within the first 24 hours after delivery. Edema or swelling in the legs during pregnancy due to increased blood volume during pregnancy and pressure from the uterus to the blood vessels in the legs, mild leg edema often occurs during pregnancy. Research abjective this research is aimed at finding out the influence of giving a talk using leaflet medium in improving the knowledge of pregnant women on swollen feet at the Public Health Center of Ngampilan, Yogyakafta.lt is a kind of pre-experiment research with one group pretest and post-test. This research is conducted at the Public Health Center of Ngampilan between July 11th and 22nd,2014. The subject of this research ls pregnant women at the respective public health center. There are 24 respondents altogether for this research. The instrument used ta collect data is in the form of a questionnaire. A paired sample t-test is used to analyze the data. The average grade of the pretest is 53.12. Meanwhile, the average grade of the post fest is 83.86. The assessment of a hed sample t-test has resulted in the p-value of 0.000<0.05 so there is a significant difference between the grades of the pretest and posttest. if graded, the knowledge increase by 30.73. ln terms of knowledge improvement, there is a significant difference between the two test groups. Giving a talk using leaflet medium is, in fact, able to improve the knowledge of pregnant women on swollen feet at the Public Health Center of Ngampilan in 2014.